(untitled) (Medico Legal Update, 2021)
Fatal neck pressure due to manual strangulation is a relatively common event. Sudden deaths that occur in the first seconds of pressure are attributed to effects of the nerve. According to leading authors, the process occurs through a reflex arc where the afferent (sensory) nerve impulses emerge in the carotid complex of the nerve endings, but not in the vagus trunk itself. On the contrary, we describe one such fatality. The body of a man in his early twenties came to attention in our Institute. According to testimonies and investigations, the victim had a domestic fight with his brother. After a verbal altercation, the victim was grabbed by the neck and immediately fell dead. During the external examination, only two small finger-nail superficial abrasions were found in the left cervical region. No other signs of violence were detected. The dissection of the neck only revealed a perineural hematoma in the left vagus trunk in the cervical tract. The cause of death was attributed to neurally mediated cardiac arrest induced by direct left vagus nerve compression.